Epidemiology and risk factors of needle stick injuries - Bijani, Behzad; Azimian, jalil; Soleimany, mohammadali; Mohammadi, navid (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim Needle stick injuries are one of the most important threats for the nursing staff in teaching hospitals. this study aimed to determine incidence, risk factors and protective factors of needle stick injuries in nursing staff. Materials and Methods In a cross sectional study, we gathered information on needle stick injuries from March 2007 up to March 2010. All nurses in Bou-aAli Sina teaching hospital (n=246) included in the study (census). A questionnaire which consisted of questions on demographic characteristics, working habits, history of related training courses, educational level, work experiences and injury-related information. Was administerd Validity and reliability of the questionnaire were assessed by content validity and test-retest (r=0.89) methods respectively. Epi Info 3.5.1 package was used for statistical analysis. Findings Needle stick injury was reported in 77 nurses out of 246 in different positions. Independent risk factors for needle stick injuries were habitual recapping of used needles and consecutive shift works. Overall 54.5% of incidents were reported to hospital infection control facilities. Male gender and younger age had significant statistical association with lower likelihood of reporting of needle stick injuries. Conclusion According to the complications of needle stick injuries, training programs in this field are one of the priorities in the teaching hospitals. In addition, decrease in consecutive shift works for nurses may have a significant impact on prevention of these injuries in nursing staff. Keywords : Needle sticks injuries, Incidence, Risk factors * Corresponding author: Assisstant Professor, faculty of Medicine, Qazvin University of Medical Sciences, Qazvin Iran E-mail: azimianj@yahoo.com REFERENCES -Abu-Gad HA Al-Turki KA (2001). Some epidemiological aspects of needle stick injuries among the hospital health care workers: Eastern Province, Saudi Arabia. European Journal of Epidemiology. 17 (5) 401-407. -Afrasiabifar A Salari M Zarifi A (2003). [Skin penetrating injuries due to the insertion of sharp medical instruments contaminated with patients’ blood or body secretion among the healthcare [stuffs] of Yasuj hospitals and the measures taken after injury, 1380]. Armaghane-Danesh, journal of yasuj university of medical scinces. 7 (28) 17-23. (Persian) -Aghadoost D et al (2007). [Occupational exposure to blood in the stuff of educational-medical centers of Kashan University of Medical Sciences in 2007].Feyz. 10 (4) 59-64 (Persian) -Aghajanloo A et al (2007). [Types and rates of occupational accidents in nursing students at nursing and midwifery colleges in Tehran].Journal of Faculty of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences. 17 (57) 11-16 (Persian) -Askarian M Shaghaghian S McLaws M (2007). Needlestick injuries among nurses of Fars province, Iran. Annals of Epidemiology. 17 (12) 988-992. -Azar Cavanagh M Burdt P Green-McKenzie J (2007). Effect of the introduction of an engineered sharps injury prevention device on the percutaneous injury rate in healthcare workers. Infection Control and Hospital Epidemiology. 28(2) 165-170. -Beltrami E et al (2000). Risk and management of blood-borne infections in health care workers. Clinical Microbiology Reviews. 13 (3) 385-407. -Boal W et al (2008). The national study to prevent blood exposure in paramedics: exposure reporting. American Journal of Industerial Medicine. 51(3) 213-222 -Clarke S Sloane D Aiken L (2002). Effects of hospital staffing and organizational climate on needlestick injuries to nurses. American Journal of Public Health. 92(7) 1115-1119. -Elmiyeh B et al (2004). Needle-stick injuries in the national health service: A culture of silence. Journal of the Royal Society of Medicine. 97 (7) 326-327. -Falagas M Karydis I Kostogiannou I (2007). Percutaneous exposure incidents of the health care personnel in a newly founded tertiary hospital: a prospective study. Public Library of Science One. 2 (2) e194. -Ippolito G et al (1999). Occupational human immunodeficiency virus infection in health care workers: Worldwide cases through September 1997. Clinical Infectious Diseases. 28(2) 365-383. -Kazemi galougahi MH (2010). Evaluation of needle stick injuries among nurses of Khanevadeh Hospital in Tehran. Iranian Journal of Nursing and Midwifery Reasearch 15 (4) 172-177. -Khalooei A et al (2010). [Study on epidemiology of needle stick injury among nursing personnel of Kerman University hospitals. Kerman, Iran in (2006-2007)]. Journal of Jahrom University of Medical Seiences. 7(3) 43-51.(Persian) -Lee JM et al (2005). Needlestick injuries in the United States. Epidemiologic, economic, and quality of life issues. Official Journal of the American Association of Occupational Health Nurses. 53(3) 117-133. -Lorentz J Hill L Samimi B (2000). Occupational needlestick injuries in a metropolitan police force. American Journal of Preventive Medicine. 18 (2) 146-150. -Lotfi R Gashtasbi A (2008). [Needle stick and sharps injuries and its risk factors among health center personnel (Astara; Iran, 2006)]. Journal of Babol University of Medical Sciences. 10(4) 71-77.(Persian) -Mahfouz AA et al (2009). Injection safety at primary health care level in south-western Saudi Arabia. Eastern Mediterranean Health Journal. 15(2) 443-450. -Makary MA et al (2007). Needlestick injuries among surgeons in training. New England Journal of Medicine. 356 (26) 2693-2699. -Mirzaee T Ravari A (2003). [Risk of recapping: Why do health care worker recap needles?]. Journal of Birjand university of medical sciences. 10 (2) 28-33. (Persian) -Nasiri E et al (2005). [The prevalence and study of the rate of needle stick injuries infected by blood in staffs of special departments of teaching and non teaching hospitals of Mazandaran province in 2003-2005]. Iranian Journal of Infectious Diseases and Tropical Medicine. 10 (29) 41-46. (Persian) -Norsayani MY Noor HI (2003). Study on incidence of needle stick injury and factors associated with this problem among medical students.Journal of Occupational Health. 45(3) 172-178.l -Nsubuga FM, Jaakkola MS (2005). Needle stick injuries among nurses in sub-Saharan Africa. Tropical Medicine & International Health. 10(8) 773-781. -Parks D et al (2000). Day-night pattern in accidental exposures to blood-borne pathogens among medical students and residents. Chronobiology International. 17 (1) 61-70. -Perry J Parker G Jagger J (2001). Percutaneous injuries in home healthcare settings. Home Healthcare Nurse. 19(6) 342-344. -Rakhshani F Heidari MT Barati S (2008). [Prevalence of needlestick injuries among the healthcare professionals in Zahedan Medical Sciences University]. Iranian Journal of Epidemiology. 4 (3) 87-91. (Persian) -Rampal L et al (2010). Needle stick and sharps injuries and factors associated among health care workers in a Malaysian hospital. European Journal of Social Sciences, 13(3) 354-362. -Shah S Merchant A Dosman J (2006). Percutaneous injuries among dental professionals in Washington State. BMC.Public Health. Doi: 10.1186/1471-2458-6-269 -Smith D et al (2006a). Epidemiology of needlestick and sharps injuries among professional Korean nurses. Journal of Professional Nursing. 22 (6) 359-366. -Smith D et al (2006b). Epidemiology of needlestick and sharps injuries among nurses in a Japanese teaching hospital. Journal of Hospital Infection. 64(1) 44-49. -Smith DR et al (2006c). Needlestick and sharps injuries among nurses in a tropical Australian hospital. International Journal of Nursing Practice. 12 (2) 71-77.